Pengaruh Ukuran Perusahaan, Leverage, dan Likuiditas terhadap Kualitas Laba dengan Profitabilitas sebagai Variabel Moderating - Vita Nurul Azizah; Asrori Asrori (Politeknik Ganesha Medan, 2022)
This research intends to find out the influence of firm size, leverage, and liquidity on earnings quality with profitability as a moderating variable. The property and real estate companies listed on Indonesia Stock Exchange for the period 2017 to 2020 is used as the population in this recearch. This study used a purposive sampling technique with 77 units of analysis obtained. The analytical technique used in this research is Ordinary Least Square (OLS) using the SPSS 25 application. The study shows that firm size have no influence on earnings quality and leverage have no influence on earnings quality, while liquidity has a significant positive influence on earnings quality. Profitability can strengthen the influence of company size on earnings quality. On the other hand, profitability can weaken the influence of leverage on earnings quality but, profitability can not strengthen the influence of liquidity on earnings quality. The conclusions of this research that liquidity has a significant positive influence on earnings quality. Profitability can strengthen the influence of firm size on earnings quality and profitability can weaken the influence of leverage on earnings quality. Suggestions for a new research are expected to add different independent variables which have influence on earnings quality